Radical Carbosulfonylation of Propellane: Synthesis of Sulfonyl β-Keto-bicyclo[1,1,1]pentanes - Wei, Yunlong; Chen, Zhiqi; Wu, Zhen; Xu, Yaohui; Wu, Xinxin; Zhu, Chen (Synthesis, 2021)
The construction of multiply functionalized bicyclo[1.1.1]pentanes (BCPs) is of high synthetic value, as they are frequently harnessed as bioisosteres of 1,3-disubstituted benzene rings, alkynes, and tert-butyl groups in medicinal chemistry. Herein, we disclose a practical radical-mediated carbosulfonylation of propellane for the synthesis of sulfonyl β-keto-substituted BCPs by using vinyl sulfonates as dual-function reagent. This protocol features broad functional group tolerance and excellent atom-economy, leading to a variety of valuable difunctionalized BCP derivatives under mild photochemical conditions.
Keywords: bicyclo[1.1.1]pentanes; propellane; sulfonylation; photochemical; C–C cleavage; radical reactions